Accuracy of episodic autobiographical memory in children with early thyroid hormone deficiency using a staged event - Willoughby, Karen A. (Dev Cogn Neurosci, 2014)
Autobiographical memory (AM) is a highly constructive cognitive process that often contains memory errors. No study has specifically examined AM accuracy in children with abnormal development of the hippocampus, a crucial brain region for AM retrieval. Thus, the present study investigated AM accuracy in 68 typically and atypically developing children using a staged autobiographical event, the Children's Autobiographical Interview, and structural magnetic resonance imaging. The atypically developing group consisted of 17 children (HYPO) exposed during gestation to insufficient maternal thyroid hormone (TH), a critical substrate for hippocampal development, and 25 children with congenital hypothyroidism (CH), who were compared to 26 controls. Groups differed significantly in the number of accurate episodic details recalled and proportion accuracy scores, with controls having more accurate recollections of the staged event than both TH-deficient groups. Total hippocampal volumes and anterior hippocampal volumes were positively correlated with proportion accuracy scores, but not total accurate episodic details, in HYPO and CH. In addition, greater severity of TH deficiency predicted lower proportion accuracy scores in both HYPO and CH. Overall, these results indicate that children with early TH deficiency have deficits in AM accuracy and that the anterior hippocampus may play a particularly important role in accurate AM retrieval.